The Study of Drug Storage Behavior in Indonesia: A Scoping Review: Studi Perilaku Penyimpanan Obat di Indonesia: Scoping Review - Richard, Tricia Andini; Hanifah, Suci; Susanto, Yuliet (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Poor home drug storage techniques can worsen the issue of antibiotic resistance, lower therapeutic efficacy, and raise the risk of toxicity. The purpose of this study was to use a scoping review technique to map the knowledge, attitudes, and practices of Indonesians with regard to drug storage. Home drug storage practices may be affected by Indonesians’ knowledge, attitudes, and habits regarding the storage of household pharmaceuticals using a scoping review methodology.Methods: This study uses a scoping review methodology. The study reviewed scientific literature that was obtained from the Google Scholar database, PLOS ONE, PubMed, Indonesia One Search, by using “Boolean.” Of the 615 records, twenty-six met the inclusion requirements.Results: According to the report, most Indonesian families keep up to five types of medications in their homes. Such as antibiotics, antipyretics, antiplatelet medications, anti-hypertensive medications, cough suppressants, antihistamines, and pain relievers. Misunderstanding was also present. The improper disposal of expired medications poses not only a health issue but also a safety one. Additionally, national programs have improved people’s awareness. During the period, education programs significantly improved drug use competence and education.Conclusion: Many Indonesian houses continue to store drugs improperly. The drug management staff are working on preventing the community from storing drugs inappropriately. Increasing education and educational initiatives are required. Indonesian families continue to face many drug-related problems; more education and training, particularly safety and more effective in the community, medical personnel, suitable storage facilities, and educational initiatives are required.